Late dacrocystitis in post endoscopic angiofibroma excision: a case report - Munjal, Manish; Arora, Priyanka; Rishi, Porshia; Sidhu, Harjinder; Munjal, Shubham; Talwar, Shivam; Sharma, Salony; Kaushal, Nimisha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Epiphora consequent to stenosis of the nasolacrimal duct, an unexpected sequela of trans nasal endoscopic angiofibroma excision was treated by a revision flap dacrocystorhinostomy.